Електрокаталітичні властивості каталізаторів, нанесених на вуглецеві нанотрубки, для кисневих електродів хімічних джерел струму - Slobodyanyuk, I. A.; Danilov, M. O.; Rusetskii, I. A.; Kolbasov, G. Ya. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
Nanocomposite electrocatalytic materials on the basis of multiwall carbon nanotubes with metals (Pt, Ni, Pb), oxides (manganese, molybdenum, chromium, cobalt, niobium) and cadmium sulphide are gained. Correlation catalytic activity of electrodes from magnitude of the coefficient «a» in the equation for Tafel reaction of oxygen evolution is detected. It is assumed that adsorption of a reagent and carrying over electrons are localized and proceed in parallel on the catalyst and the carrying agent, and reagent particles diffuse through a catalyst and carrying agent phase boundary. The leading-out is drawn that for carbon nanotubes, with a low adsorption energy of oxygen, it is necessary to apply the catalyst with a high adsorption energy of molecular oxygen, and consequently with great value of an overstrain in allocation reaction to it of molecular oxygen.